Perturbing phytoplankton: a tale of isotopic fractionation in two coccolithophore species - Rickaby, R; Henderiks, J; Young, J (Coppernicus Publications, 2010)
No two species of coccolithophore appear to respond to perturbations of carbonate chemistry in the same way. Here, we show that the degree of malformation, growth rate and stable isotopic composition of organic matter and carbonate produced by two contrasting species of coccolithophore (Gephyrocapsa oceanica and Coccolithus pelagicus ssp. braarudii) are indicative of differences between their photosynthetic and calcification response to changing dissolved inorganic carbon (DIC) levels (ranging from ~1100 to ~7800 μmol kg⁻¹) at constant pH (8.13±0.02). G.oceanica thrived under all conditions of DIC, showing evidence of increased growth rates at higher DIC, but C. braarudii was detrimentally affected at high DIC showing signs of malformation, and decreased growth rates. The carbon isotopic fractionation into organic matter and the coccoliths suggests that C. braarudii utilises a common internal pool of carbon for calcification and photosynthesis but G. oceanica relies on independent supplies for each process. All coccolithophores appear to utilize bicarbonate as their ultimate source of carbon for calcification resulting in the release of a proton. But, we suggest that this proton can be harnessed to enhance the supply of aqueous dissolved carbon dioxide (CO₂(ag)) for photosynthesis either from a large internal bicarbonate ion (HCO₃⁻) pool which acts as a PH buffer (C. braarudii), or pumped externally to aid the diffusive supply of CO₂ across the membrane from the abundant HCO₃⁻ (G. oceanica), likely mediated by an internal and external carbonic anhydrase, respectively. Our simplified hypothetical spectrum of physiologies may provide a context to understand different species response to changing pH and DIC, the species-species εp and calcite "vital effects", as well as accounting for geological trends in coccolithophore cell size.